Investigation of flow uniformity and pressure recovery in a turning diffuser by means of baffles - Noh@Seth, Nur Hazirah; Nordin, Normayati; Othman, Safiah; Raghavan, Vijay R. (Trans Tech Publications, 2014)
Turning diffuser is an engineering device that is widely used in the industry to reduce the flow velocity as well as change the direction of the flow. Having a curvature shape causes its performance to decrease in terms of pressure recovery (Cp) and flow uniformity (σu). Therefore, this study presents the work done in designing baffles to be installed in the turning diffuser with ratio of AR=2.16 to improve the flow uniformity and pressure recovery. It also aims to investigate the mechanism of flow structure and pressure recovery in turning diffusers by means of turning baffles. The results with varying inflow Reynolds number (Rein) between 5.786E+04 – 1.775E+05 have been experimentally tested and compared with previous study. Particle image velocimetry (PIV) was used to determine the flow uniformity. On the other hand, a digital manometer provided the average static pressure of the inlet and outlet of turning diffuser. The best produced pressure recovery of Cp=0.526 were recorded when the system were operated at the highest Reynolds number tested Rein=1.775E+05. This result shows an improvement up to 54.625% deviation from previous study with Cp=0.239. The flow uniformity also shows an improvement of 47.127% deviation from previous study at the same Rein with σu=3.235 as compared to previous study σu=6.12.